Ensuring safety at sea : the Southern Ocean and the South China Sea - Sam, Bateman (2012)
The Southern Ocean and the South China Sea are very different marine environments but both face high risks of incidents at sea that endanger safety and damage international relations. Restraint is required for good order and amicable relations between parties involved.